Electron-beam-excited Penning-removal plasma laser λ = 585.3 nm on dense neon-containing mixtures; Journal of the Optical Society of America B; Vol. 3, iss. 7 - Bunkin F. V.; Derzhiev V. I.; Mesyats G. A. Gennady Andreyevich; Skakun V. S.; Tarasenko V. F. Victor Fedotovich; Yakovlenko S. I. (1986, 1986)
Laser action is obtained on the transition in Ne of λ = 585.3 nm by pumping dense Ne–H2 and Ne–He–Ar mixtures (P = 0.2 − 3 atm) with an electron beam (jmax = 40 A/cm2, τbeam = 80 nsec). Inversion occurs because of the removal of the lower active state by the Penning reactions of Ne with H2 and Ar. The total output energy is about 2 mJ; the output energy density is about 10−5 J/cm3 for 0.1% lasing efficiency estimated from the calculated energy input